Theoretical Foundation for a Learning Rate Budget - Kantor, Paul B.; Zangwill, Willard I. (Management Science, 1991)
A conceptualization of production learning is proposed, which resolves costs into groups characterized by the rate at which the costs can be reduced. These groups may correspond to learning in process, materials or technology. This approach suggests a new budget methodology, the Learning Rate Budget (LRB), which combines activities with similar learning rates to facilitate planning, forecasting, bidding, accountability, and management control. This new conceptualization of cost progress rests on three postulates concerning the budget, the technology and a finite basis for the learning curve. This paper explores these postulates, presents the LRB, and summarizes the empirical study that led to this concept.